2010
DOI: 10.1016/j.ejphar.2010.02.045
|View full text |Cite
|
Sign up to set email alerts
|

The plasma carnitine concentration regulates renal OCTN2 expression and carnitine transport in rats

Abstract: Previous findings in rats and in human vegetarians suggest that the plasma carnitine concentration and/or carnitine ingestion may influence the renal reabsorption of carnitine. We tested this hypothesis in rats with secondary carnitine deficiency following treatment with N-trimethyl-hydrazine-3-propionate (THP) for 2 weeks and rats treated with excess L-carnitine for 2 weeks. Compared to untreated control rats, treatment with THP was associated with an approximately 70% decrease in plasma carnitine and with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 32 publications
2
5
0
1
Order By: Relevance
“…Furthermore, previous studies showed that serum carnitine levels were altered after VPA treatment (Moreno et al, 2005). Carnitine was also reported to alter Octn2 expression, which might be involved in Octn2 alteration in the present study (Schürch et al, 2010).…”
Section: Discussionsupporting
confidence: 67%
“…Furthermore, previous studies showed that serum carnitine levels were altered after VPA treatment (Moreno et al, 2005). Carnitine was also reported to alter Octn2 expression, which might be involved in Octn2 alteration in the present study (Schürch et al, 2010).…”
Section: Discussionsupporting
confidence: 67%
“…carnitine administration (Bartels et al 1992), which is not the case for skeletal muscle (Stephens et al 2006), this also supports the suggestion that heart tissue exhibits greater sensitivity to acute changes in plasma and tissue carnitine availability. The present observations are also consistent with the report that meldonium does not affect OCTN2 mRNA expression in mixed-fibre skeletal muscles (quadriceps femoris; Schurch et al 2010), suggesting that muscle OCTN2 transcription does not respond to acute plasma and tissue carnitine depletion, nor to increased OCTN2 substrates, such as meldonium and γ-butyrobetaine, which are elevated in the plasma as a consequence of meldonium administration (Liepinsh et al 2006;Liepinsh et al 2011b). However, under conditions of chronically reduced plasma and muscle carnitine availability, as occurs in long-standing human vegetarianism, a decline in muscle OCTN2 protein expression can be expected in humans .…”
Section: Discussionsupporting
confidence: 92%
“…The present observations are also consistent with the report that meldonium does not affect OCTN2 mRNA expression in mixed‐fibre skeletal muscles (quadriceps femoris; Schurch et al . ), suggesting that muscle OCTN2 transcription does not respond to acute plasma and tissue carnitine depletion, nor to increased OCTN2 substrates, such as meldonium and γ‐butyrobetaine, which are elevated in the plasma as a consequence of meldonium administration (Liepinsh et al . ; Liepinsh et al .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct inhibition of CPT I or to an increase in malonyl-CoA content, a decrease in L-carnitine concentration in heart tissues was found to be one of the most effective ways to decrease the activity of CPT I. For a long time, the only non-toxic and effective compound that decreased the concentration of L-carnitine and consequently had protective effects against cardiovascular diseases was meldonium (Dambrova et al, 2002;Schurch et al, 2010). In comparison, the new compound Methyl-GBB is 10-20 times more potent as an inhibitor of BBOX and OCTN2, and it was more effective in reducing the L-carnitine concentration in blood plasma and tissues.…”
Section: Figurementioning
confidence: 99%